Evaluation of Budget Realization in The Financial Statements of Bambalamotu Sub-District Based on PSAP No. 02 - Shakira, Iin; Usman, Ernawaty; Sugianto; Jamaluddin (Equivalent : Journal of Economic, Accounting and Management, 2025)
This study aims to examine the budget realization in the financial reports of Bambalamotu Sub-district against the implementation of Government Accounting Standards Statement (PSAP) No. 02. From the analysis, it is seen that even though not all of the items that are needed in PSAP No. 02 are presented-such as revenues, transfers, and net financing-the report preparation has been adapted to the actual fiscal situation of the area and still accommodates the principles of transparency and accountability. These modifications illustrate the necessity for contextualized and flexible application of accounting standards, specifically in areas of weak fiscal capacity. This research also constructs further the importance of the computerized system support for financial reporting but clarified that inadequate human resources continue to be the primary constraint in maximizing the system. The findings' implications assure that reporting that is customized according to local requirements and capacity can continue to be effective in the fulfillment of public accountability goals. The research is limited in the sense of having narrow geographical coverage and sparse primary data.